2021
DOI: 10.1063/5.0030809
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy for carbon nanotube applications

Abstract: The use of Raman spectroscopy for carbon nanotube applications is presented here as a tutorial review. After introducing the relevant basic aspects of Raman spectroscopy of graphene-related materials, we will discuss how to use the Raman spectral features for practical purposes of controlling and characterizing nanotube properties relevant for applied materials and devices. Advanced techniques with potential to enhance the relevance of Raman spectroscopy application in the carbon nanotube field are also presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
161
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(168 citation statements)
references
References 229 publications
4
161
0
3
Order By: Relevance
“…The non-functionalized CNT evaluated by Bogas et al [19] showed an I D /I G ratio of 0.85. These Raman results show that CNT functionalized with the carboxyl groups have a higher amount of localized defects in the sp 2 network compared to non-functionalized CNT [20]. This suggests that the ultrasonication parameters used for dispersing non-functionalized CNT should be carefully evaluated to verify that they are adequate in dispersing functionalized CNT.…”
Section: Methodsmentioning
confidence: 94%
“…The non-functionalized CNT evaluated by Bogas et al [19] showed an I D /I G ratio of 0.85. These Raman results show that CNT functionalized with the carboxyl groups have a higher amount of localized defects in the sp 2 network compared to non-functionalized CNT [20]. This suggests that the ultrasonication parameters used for dispersing non-functionalized CNT should be carefully evaluated to verify that they are adequate in dispersing functionalized CNT.…”
Section: Methodsmentioning
confidence: 94%
“…The G band split into G − band and G + band (Figure 3), which is usually observed in carbon nanotubes (CNT) as a result of curvature [83]. This splitting has also been observed when graphene sheets are strained [84], wrinkled [85], or folded and scrolled [86].…”
Section: Deposition On Zno/ag Substratesmentioning
confidence: 79%
“…The radial breathing mode(RBM) bands are a useful diagnostic tool for confirming the presence of SWCNTs as well as depend on chirality and diameter of SWCNTs. The RBM frequency is inversely proportional to the diameter of the tube, making it an important feature for determining the diameter distribution in a sample and calculated using the expression ω RBM =A/d t +B, where A and Bare determined experimentally [6], in [24] authors choice has a very good quantitative agreement with other calculations 2 227 1…”
Section: Iii2 Raman Scatteringmentioning
confidence: 79%
“…where C env quantifies the effect of the environment on the RBM frequency and for most samples in the literature present 0.056 nm −2 [24]. The RBM bands of SWCNT were observed at 169 cm −1 and 168 cm −1 for pristine and post irradiation accordingly.…”
Section: Iii2 Raman Scatteringmentioning
confidence: 98%